A vaginal estradiol softgel capsule, TX-004HR, has negligible to very low systemic absorption of estradiol: Efficacy and pharmacokinetic data review. (May 2017) - Simon, James A.; Archer, David F.; Constantine, Ginger D.; Pickar, James H.; Amadio, Julia M.; Bernick, Brian; Graham, Shelli; Mirkin, Sebastian
Highlights: TX-004HR is a new, investigational drug for treating vulvar-vaginal atrophy (VVA). In a phase 3 study, TX-004HR improved vaginal physiology and symptoms of vulvar-vaginal atrophy. The pharmacokinetics of TX-004HR show negligible to very low estradiol systemic levels. TX-004HR had local vaginal efficacy of estrogens with minimal systemic absorption. TX-004HR may be another option for treating symptomatic postmenopausal vulvar-vaginal atrophy. Abstract: This paper reviews the efficacy, safety, and systemic absorption of estradiol with TX-004HR, an investigational, low-dose 17β-estradiol vaginal softgel capsule, designed to treat vulvar and vaginal atrophy (VVA) in postmenopausal women, with an improved user experience. In phase 2 (NCT02449902) and phase 3 REJOICE (NCT02253173) studies, TX-004HR significantly improved the proportions of vaginal superficial and parabasal cells and vaginal pH, and in the phase 3 study decreased the severity of dyspareunia, vaginal dryness, and vulvar and/or vaginal itching or irritation. In two randomized, phase 1 trials, estradiol Cmax and AUC0-24 were significantly lower with 10 μg and 25 μg TX-004HR than with the same doses of an approved vaginal estradiol tablet. A substudy ( n  = 72) of the REJOICE trial showed that estradiol Cavg and AUC0-24 with 4 μg and 10 μg TX-004HR were not different from placebo on days 1 and 14. While TX-004HR 25 μg was associated with higher Cavg and AUC0-24 versus placebo on days 1 and 14, these levels remained within the postmenopausal range. Estradiol day-84 values for all three doses were not different from placebo, demonstrating no estradiol accumulation. All TX-004HR doses were well tolerated and had an acceptable safety profile in all reviewed studies. The local vaginal efficacy of TX-004HR was significantly better than that of placebo, while the overall safety profile was similar to that of placebo. Negligible to very low systemic estradiol absorption was observed whether given at 4, 10, or 25 μg. If approved, TX-004HR may be an alternative option for women with symptomatic VVA without increasing mean systemic estradiol absorption above postmenopausal levels.